2000
DOI: 10.1359/jbmr.2000.15.7.1257
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase-3 (MMP-13) and Integral Membrane Protein 2a (Itm2a) are Marker Genes of Chondrogenic/Osteoblastic Cells in Bone Formation: Sequential Temporal, and Spatial Expression of Itm2a, Alkaline Phosphatase, MMP-13, and Osteocalcin in the Mouse

Abstract: Endochondral bone formation requires the action of cells of the chondrocytic and osteoblastic lineage, which undergo continuous differentiation during this process. To identify subpopulations of resting, proliferating, and hypertrophic chondrocytes and osteoblasts involved in bone formation, we have identified here two novel marker genes present in endochondral and intramembranous ossification. Using Northern blot analysis and in situ hybridization on parallel sections of murine embryos and bones of newborn mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 37 publications
7
94
0
2
Order By: Relevance
“…In these cells, the major collagenase expressed at the primary and secondary sites of ossification is MMP13. Detectable as early as 14.5 days of embryonic development in mice, MMP13 is highly expressed in the lower zone of hypertrophic cartilage, where its expression colocalizes with that of type X collagen [24]. At the chondroosseous junction, MMP13 is expressed by the newly recruited osteoblasts adjacent to tartrateresistant acid phosphatase (TRAP)-positive cells [25].…”
Section: Endochondral Ossification and Mmp Expressionmentioning
confidence: 99%
“…In these cells, the major collagenase expressed at the primary and secondary sites of ossification is MMP13. Detectable as early as 14.5 days of embryonic development in mice, MMP13 is highly expressed in the lower zone of hypertrophic cartilage, where its expression colocalizes with that of type X collagen [24]. At the chondroosseous junction, MMP13 is expressed by the newly recruited osteoblasts adjacent to tartrateresistant acid phosphatase (TRAP)-positive cells [25].…”
Section: Endochondral Ossification and Mmp Expressionmentioning
confidence: 99%
“…Chondrocytes then withdraw from the cell cycle and begin to increase their cell volume until reaching the fully differentiated state of hypertrophic chondrocytes. Transition from a proliferating to a hypertrophic phenotype involves numerous changes in gene expression, for example the induction of the collagen X (4, 5), matrix metalloproteinase 13 (6,7), and bone sialoprotein (BSP) 1 (8 -10) genes. The latter two genes are also expressed by osteoblasts, suggesting similar biological properties of hypertrophic chondrocytes and osteoblasts.…”
mentioning
confidence: 99%
“…Earlier reports (Tuckermann et al, 2000) indicated that expression of Itm2a is upregulated across a zone of long bone growth plates that contains resting and proliferative chondrocytes. The expression of the gene did not overlap with other markers of endochondral ossification (MMP-13, alkaline phosphatase and osteocalcin).…”
Section: Discussionmentioning
confidence: 97%
“…Based on our previous studies that identified Itm2a as a novel marker for chondrogenic differentiation (Tuckermann et al, 2000), the present study investigated the expression of Itm2a in different cell lineages committed to chondrogenesis and a possible role of Itm2a in endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation